Nuclear transport of nicotinamide phosphoribosyltransferase is cell cycle-dependent in mammalian cells, and its inhibition slows cell growth - Svoboda, Petr; Krizova, Edita; Sestakova, Sarka; Vapenkova, Kamila; Knejzlik, Zdenek; Rimpelova, Silvie; Rayova, Diana; Volfova, Nikol; Krizova, Ivana; Rumlova, Michaela; Sykora, David; Kizek, Rene; et al. (The Journal of biological chemistry, 2019)
Nicotinamide phosphoribosyltransferase (NAMPT) is located in both the nucleus and cytoplasm and has multiple biological functions including catalyzing the rate-limiting step in NAD synthesis. Moreover, up-regulated NAMPT expression has been observed in many cancers. However, the determinants and regulation of NAMPT's nuclear transport are not known. Here, we constructed a GFP-NAMPT fusion protein to study NAMPT's subcellular trafficking. We observed that in unsynchronized 3T3-L1 preadipocytes, 25% of cells had higher GFP-NAMPT fluorescence in the cytoplasm, and 62% had higher GFP-NAMPT fluorescence in the nucleus. In HepG2 hepatocytes, 6% of cells had higher GFP-NAMPT fluorescence in the cytoplasm, and 84% had higher GFP-NAMPT fluorescence in the nucleus. In both 3T3-L1 and HepG2 cells, GFP-NAMPT was excluded from the nucleus immediately after mitosis and migrated back into it as the cell cycle progressed. In HepG2 cells, endogenous, untagged NAMPT displayed similar changes with the cell cycle, and in nonmitotic cells, GFP-NAMPT accumulated in the nucleus. Similarly, genotoxic, oxidative, or dicarbonyl stress also caused nuclear NAMPT localization. These interventions also increased poly(ADP-ribosyl) polymerase and sirtuin activity, suggesting an increased cellular demand for NAD. We identified a nuclear localization signal in NAMPT and amino acid substitution in this sequence (424RSKK to ASGA), which did not affect its enzymatic activity, blocked nuclear NAMPT transport, slowed cell growth, and increased histone H3 acetylation. These results suggest that NAMPT is transported into the nucleus where it presumably increases NAD synthesis required for cell proliferation. We conclude that specific inhibition of NAMPT transport into the nucleus might be a potential avenue for managing cancer.
Keywords: Poly(ADP-ribose) Polymerases; Sirtuins; buněčné jádro; buňky Hep G2; akrylamidy; 3T3-L1 Cells; NAD; aktivní transport - buněčné jádro; poly(ADP-ribosa)polymerasy; kontrolní body buněčného cyklu; Mutagenesis, Site-Directed; Oxidative Stress; Mice; Cell Proliferation; Hep G2 Cells; Acrylamides; Cell Cycle Checkpoints; sirtuiny; histony; mutageneze cílená; Animals; Cell Nucleus; Histones; cytoplazma; Piperidines; zvířata; Humans; Active Transport, Cell Nucleus; nikotinamidfosforibosyltransferasa; Recombinant Fusion Proteins; rekombinantní fúzní proteiny; viabilita buněk; Cell Survival; myši; proliferace buněk; Cytoplasm; oxidační stres; Nicotinamide Phosphoribosyltransferase; piperidiny; lidé; buňky 3T3-L1